2011
DOI: 10.1007/s00464-011-1933-5
|View full text |Cite
|
Sign up to set email alerts
|

Completely laparoscopic versus open gastrectomy for early and advanced gastric cancer: a matched cohort study

Abstract: In this preliminary report, with 52% of advanced tumor, the 3-year overall and stage-by-stage survival was comparable for laparoscopic and open curative gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 48 publications
4
47
1
4
Order By: Relevance
“…Francescutti and colleagues 27 have reported the only previous Canadian experience, but they included patients with benign lesions as well as those with malignant ones. All comparative studies have reported decreased or similar early postoperative morbidity with LAG ranging from 0% to 26%, [15][16][17][26][27][28][29]31 which compares with our results. Other benefits of the laparoscopic ap proach, including decreased time to ambulation and resumed diet, decreased consumption of analgesia and a shorter length of stay, have been reported in these studies.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Francescutti and colleagues 27 have reported the only previous Canadian experience, but they included patients with benign lesions as well as those with malignant ones. All comparative studies have reported decreased or similar early postoperative morbidity with LAG ranging from 0% to 26%, [15][16][17][26][27][28][29]31 which compares with our results. Other benefits of the laparoscopic ap proach, including decreased time to ambulation and resumed diet, decreased consumption of analgesia and a shorter length of stay, have been reported in these studies.…”
Section: Discussionsupporting
confidence: 88%
“…Others reported no difference between the laparoscopic and open approaches. 15,16,[26][27][28][29][30][31]33 In a meta-analysis of RCTs comparing laparoscopic and open approaches for early gastric cancer, Ohtani and colleagues 9 concluded that there was a lesser number of LNs with laparoscopy. Debate is still ongoing about the extent of the lymphadenectomy and the number of LNs needed in the specimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los pacientes con carcinoide tipo III tienen mayores posibilidades de recidiva dependiendo de su etapificación y variables histopatológicas como las ya comentadas, siendo en este grupo en donde debemos tener mayor cautela. Nuestra experiencia inicial en cáncer gástrico y gastrectomía laparoscópica presenta buenos resultados a 3 años de seguimiento al comparar con cirugía abierta 22 , sin embargo, en esta patología aún debemos juntar un mayor número de casos y con seguimiento a más largo plazo antes de afirmar su real ventaja.…”
Section: Discussionunclassified
“…First, MIS techniques are being used in more radical but less invasive procedures, such as totally laparoscopic distal gastrectomy or laparoscopic total gastrectomy with D1+ or D2 lymphadenectomy. These procedures are comparable to conventional open surgery and can be performed even in patients with advanced gastric cancer (AGC) [21][22][23] . Second, MIS is being employed for function-preserving surgery, including pylorus-preserving gastrectomy (PPG), proximal gastrectomy, and limited gastrectomy with sentinel node navigation surgery.…”
Section: Abstract: Gastric Cancer; Minimally Invasive Surgery; Laparmentioning
confidence: 99%